Bamboo Diversity in Sumba Island - ELIZABETH A. WIDJAJA; KARSONO KARSONO (Society for Indonesian Biodiversity, 2005)
Bamboo is one of the economic plant which grow widely in the villages and have been used by the local people in the villages. Indonesia has about 10% of the world bamboo, 50% among them was endemic to Indonesia. According Widjaja (2001) Lesser Sunda Island which consists of Lombok, Sumbawa, Flores, Timor, Sumba and other small island eastern of Flores has 14 bamboo species, however, the information from the Sumba Island was lacking because of lacking data from this area except one species which was proposed by S. Soenarko in 1977 where the type specimens was collected by Iboet 443 in 1925. To fullfill data from the Sumba Island, an exploration tothis area has been conducted on July 2003. The observation was done in West Sumba and East Sumba District, especially in two natioal parks at both districts. According to this inventory study in the Sumba Island, there were 10 bamboo species in Sumba Island, 1 species among them (Dinochloa sp.) was a new species which has not been collected before, whereas the other species (Dinochloa kostermansiana) has a new addition record from this area. The bamboo species in Sumba Island were Bambusa blumeana, Bambusa vulgaris, Dendocalamus asper, Dinochloa kostermansiana, Dinochloa sp., Gigantochloa atter, Nastus reholtumianus, Phyllostachys aurea, Schisotachyum brachycladum and Schizostachyum lima. From 10 recorded species, the genera Dinochloa and Nastus grow wild in the forest, whereas another species grow widly or cultivated in the garden. Furthermore, the genus Dinochloa was the only genus grow climbing. The endemic species found in Sumba Island was Nastus reholttumianus, whereas Dinochloa kostermansiana was also found in Flores Island.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: biodiversity, bamboo, Sumba Island.